119구급대원을 대상으로 테이핑의 중재 후 근 활성도에 미치는 영향 - 신동민(Dong-min Shin); 김근희(Keun-Hee Kim); 조병준(Byung-Jun Cho) (한국컴퓨터정보학회논문지, 2018)
In this paper, we propose a taping therapy as effective intervention for patients with the back pain. The purpose of this study is to investigate the effects of taping intervention on the VAS evaluated score and he muscular activation degree among 119 paramedics with musculoskeletal injury. In order to achieve the purpose of the study, data was collected from 15 paramediecs in the paramedics department of 3 fire stations under J city's fire defense headquarters. The following results can be obtained by measuring the subjective, the back muscle strength and the buckling-anteflexion before and after the taping for 15 119 paramedics. Through the verification experiment of taping effect to paramedics during the stretcher lifting in this study the VAS evaluated score for the backache are 1.67±0.62 before and 0.80±0.68 after the application of taping which show statistically significant decrease(p<0.05). In the experimentof joint operation range the measured buckling anteflexion length are 14.62cm±4.89 before and 16.41cm±4.11cm after the application of taping which show statistically meaningful difference(p<0.05). In the comparison of muscle activity about paramedics erector spinae(ES) shows the meaningful decrease and external obliques(EO) displays the significant increase. Erector spinae(ES) and internal obliques(IO) show the increasing trend in the muscle activity although they are not significant. the muscle activity for the erector spinae is lowered so that the contribution to the force required for the extensor during the stretcher lifting is resultingly reduced to have the effects of enhancing the activity of abdominal muscles. KCI Citation Count: 0